Water-based paint suitable for cement floor and preparation method of water-based paint

By using a combination formula of components such as acrylic emulsions in water-based coatings, a semi-interpenetrating network structure and physical cross-linking network are constructed, which solves the poor interface bonding, incomplete film formation and insufficient wear resistance of water-based coatings in cement floor applications. These problems have achieved excellent adhesion, wear resistance and weather resistance, and improved storage stability and construction convenience.

CN119264714AActive Publication Date: 2025-01-07ZHEJIANG XINGHUI NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411632335.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-07
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

In the application of cement floors, existing water-based coatings have problems such as poor interface bonding, incomplete film formation, insufficient wear and toughness, poor water resistance and poor storage stability.

Method used

Use acrylic emulsion, N-hydroxyethylacrylamide, modified nanosilica, graphene oxide, polyethylene glycol methyl ether methacrylate, 2-(dimethylamino) ethyl methacrylate, defoaming agent Combination formulas of , leveling agent, wetting agent, film forming additive, thickening agent, mildew-proof fungicide and multi-level filler, build semi-interpenetrating network structure and physical crosslinking through molecular design and multi-component synergistic effect. Network, realizes interface integration and performance regulation.

Benefits of technology

It significantly improves the adhesion, wear resistance, toughness and weather resistance of the coating, ensures stable performance under different environmental conditions, and improves storage stability and construction convenience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005136244600000151
    Figure BDA0005136244600000151
  • Figure BDA0005136244600000152
    Figure BDA0005136244600000152
Patent Text Reader

Abstract

The invention relates to the technical field of water-based paint, in particular to water-based paint suitable for cement floors and a preparation method thereof.The water-based paint is prepared from, by weight, 60-80 parts of acrylic emulsion, 3-5 parts of N-hydroxyethyl acrylamide, 2-4 parts of modified nano silicon dioxide and 0.1-0.3 part of graphene oxide. The invention relates to an anti-mildew coating, which is prepared from the following components in parts by weight: 1 to 2 parts of polyethylene glycol methyl ether methacrylate, 2 to 4 parts of 2-(dimethylamino) ethyl methacrylate, 0.2 to 0.6 part of defoaming agent, 0.5 to 1 part of flatting agent, 0.3 to 0.6 part of wetting agent, 4 to 10 parts of coalescing agent, 0.5 to 1.5 parts of thickening agent, 0.1 to 0.2 part of anti-mildew bactericide and 20 to 40 parts of filler, the adhesive force of the coating and a cement base material reaches 0 grade, and the performance is kept stable after water soaking resistance; the wear resistance is improved by more than 3 times compared with the traditional water-based paint, and meanwhile, good toughness is kept; and ideal film formation can be realized within the range of 5-40 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water-based coatings, and in particular to a water-based coating suitable for cement floors and a preparation method thereof. Background Art

[0002] As one of the most common substrates in industrial and civil buildings, the surface protection of cement floors has always been the focus of the coatings industry. Although traditional solvent-based epoxy resin coatings have excellent wear resistance and adhesion, they have high volatile organic compound (VOC) content, which poses serious harm to the environment and human health. In response to environmental protection requirements, water-based coatings have gradually become a research hotspot. However, there are still many technical difficulties in the application of existing water-based coatings in cement floors:

[0003] First, due to the high alkalinity and porous properties of the cement substrate surface, the interface bonding between traditional water-based coatings and the substrate is poor, which is prone to blistering, shedding and other problems. Although the interface bonding can be improved by adding coupling agents, a single chemical bonding method is difficult to cope with complex service environments.

[0004] Secondly, the film-forming process of water-based coatings is significantly affected by environmental conditions, especially in low temperature or high humidity environments, which can easily lead to defects such as incomplete film-forming and cracking. Existing technologies improve this problem by adding film-forming aids, but this often affects the final performance of the coating.

[0005] Thirdly, the mechanical properties of water-based coatings, especially wear resistance and toughness, are still far behind those of solvent-based coatings. Although the hardness can be increased by increasing the cross-linking density, it often makes the coating brittle and the actual application effect is not ideal.

[0006] In addition, existing water-based coatings have poor water resistance, which is directly related to the presence of hydrophilic components. Although water resistance can be improved by hydrophobic modification, it often affects the stability and construction performance of the coating.

[0007] Finally, traditional water-based coatings have poor storage stability, fillers are prone to sedimentation, and require frequent stirring, which brings many inconveniences to practical applications. Summary of the invention

[0008] In view of the above problems, the present invention proposes an innovative water-based paint formula suitable for cement floors and a preparation method thereof.

[0009] The object of the present invention is to provide a water-based paint suitable for cement floors, wherein the water-based paint comprises the following components in parts by weight:

[0010] Acrylic emulsion 60-80 parts,

[0011] 3-5 parts of N-hydroxyethyl acrylamide,

[0012] 2-4 parts of modified nano silicon dioxide,

[0013] Graphene oxide 0.1-0.3 parts,

[0014] 1-2 parts of polyethylene glycol methyl ether methacrylate,

[0015] 2-(dimethylamino)ethyl methacrylate 2-4 parts,

[0016] Defoaming agent 0.2-0.6 parts,

[0017] 0.5-1 part of leveling agent,

[0018] Wetting agent 0.3-0.6 parts,

[0019] 4-10 parts of film-forming aid,

[0020] Thickener 0.5-1.5 parts,

[0021] 0.1-0.2 parts of antifungal fungicide,

[0022] 20-40 parts of filler.

[0023] Specifically, the acrylic emulsion includes pure acrylic emulsion and water-based acrylic ester emulsion, and the weight ratio of the pure acrylic emulsion to the water-based acrylic ester emulsion is 4:1; wherein the pure acrylic emulsion is styrene acrylic emulsion, and the water-based acrylic ester emulsion is selected from random copolymers of methyl methacrylate, ethyl acrylate and vinyl acetate.

[0024] Specifically, the modified nano-silica is nano-silica modified with (3-glycidylpropoxy)trimethoxysilane, and the particle size of the nano-silica is 20-30 nm.

[0025] Specifically, the thickener is quaternary ammonium salt-modified hydroxyethyl cellulose, the mildew and fungicide includes a mixture of 2-methyl-4-isothiazoline-3-one and 1,2-benzisothiazol-3(2H)-one, with a weight ratio of 1:2, and the filler includes modified calcium carbonate, nano zinc oxide and hollow glass microspheres, with a weight ratio of 3:1:1.

[0026] Specifically, the number of repeating units of the polyethylene glycol segment in the polyethylene glycol methyl ether methacrylate is 45-50, the defoaming agent is a quaternary ammonium salt of organic silicon, the leveling agent is polydimethylsiloxane, and the wetting agent is polyoxyethylene ether.

[0027] Specifically, the film-forming aid is selected from a mixture of lauryl alcohol ester and propylene glycol methyl ether, and the weight ratio of the lauryl alcohol ester to propylene glycol methyl ether is 1:1.

[0028] A method for preparing the water-based coating comprises the following steps:

[0029] (1) Preparation of modified nano-silicon dioxide:

[0030] The nano-silica was dried in vacuum at 105 °C for 4 h;

[0031] An ethanol / water mixed solution was prepared, wherein the volume ratio of ethanol to water was 8:2;

[0032] Add (3-glycidylpropoxy)trimethoxysilane to the mixed solution and adjust the pH to 4-5;

[0033] Stir at room temperature for 30 min for pre-hydrolysis;

[0034] The pretreated nano-silica was dispersed in ethanol and ultrasonically dispersed for 15 min;

[0035] Slowly add the pre-hydrolyzed silane coupling agent solution, raise the temperature to 60°C, and stir to react for 4 hours;

[0036] The mixture was centrifuged, washed with ethanol three times, dried under vacuum at 60 °C for 12 h, and ground through a 200-mesh sieve;

[0037] (2) Preparation of water-based coatings:

[0038] Mix the acrylic emulsion with N-hydroxyethyl acrylamide at a stirring speed of 400-600 r / min;

[0039] Add the modified nano-silicon dioxide and graphene oxide obtained in step (1), and disperse by ultrasonic for 15-20 minutes;

[0040] Add polyethylene glycol methyl ether methacrylate and 2-(dimethylamino)ethyl methacrylate in sequence, and control the temperature at 45-50°C;

[0041] Add thickener and filler in sequence and stir for 3 minutes;

[0042] Add defoamer, film-forming aid and leveling agent dropwise at a rate of 0.5-1 g / min and continue stirring for 30 min.

[0043] Specifically, in the step (2), when polyethylene glycol methyl ether methacrylate and 2-(dimethylamino)ethyl methacrylate are added, nitrogen protection is used.

[0044] Specifically, in the step (2), when adding the modified nano-silica and graphene oxide, the dispersion temperature is controlled at 30-35°C.

[0045] Specifically, the modified calcium carbonate is stearic acid-modified ultrafine calcium carbonate with a particle size of 0.7-1.2 μm; the particle size of the nano zinc oxide is 30-50 nm; the particle size of the hollow glass microsphere is 40-60 μm, and the density is 0.21-0.25 g / cm 3 .

[0046] The purpose of the present invention is to develop a new waterborne coating system to solve the above technical problems. The system achieves excellent comprehensive performance through molecular design and multi-component synergy:

[0047] First, a semi-interpenetrating network structure was constructed at the molecular level by introducing N-hydroxyethyl acrylamide with active double bonds. This component can not only copolymerize with acrylate, but its hydroxyl and amide groups can also form multiple hydrogen bonds with the cement matrix, significantly improving the interface bonding.

[0048] Secondly, a special nanocomposite system is used, including silica and graphene oxide modified by (3-glycidylpropoxy)trimethoxysilane. This composite filler not only provides a multi-scale reinforcement effect, but also forms a unique physical cross-linking network, which significantly improves the comprehensive mechanical properties of the coating.

[0049] It is worth mentioning that the present invention introduces the pH-responsive component 2-(dimethylamino)ethyl methacrylate into the cement floor coating system for the first time. This component promotes the deformation of emulsion particles in the alkaline environment at the beginning of construction, and gradually increases the cross-linking density as the pH decreases during the cement hydration process, thus achieving dynamic regulation of performance.

[0050] In terms of interface engineering, the present invention uses polyethylene glycol methyl ether methacrylate as an amphiphilic regulator, and its unique molecular structure forms an orderly arrangement at the interface, which not only improves the compatibility of the system, but also provides additional physical cross-linking points.

[0051] In addition, the storage stability problem was successfully solved through the synergistic effect of quaternary ammonium salt-modified hydroxyethyl cellulose and the multi-stage filler system. The modified thickener provides sufficient viscosity to prevent sedimentation under low shear, and exhibits shear thinning behavior under high shear, ensuring good construction performance.

[0052] Compared with the prior art, the water-based coating suitable for cement floors and the preparation method thereof of the present invention can achieve the following beneficial effects:

[0053] 1. Excellent interface performance: The adhesion between the coating and the cement substrate reaches level 0, and the performance remains stable after water immersion;

[0054] 2. Excellent mechanical properties: wear resistance is more than 3 times higher than that of traditional water-based coatings, while maintaining good toughness;

[0055] 3. Outstanding adaptability: ideal film formation can be achieved within the range of 5-40°C, and is insensitive to the moisture content of the substrate;

[0056] 4. Excellent durability: There is no obvious performance degradation in the weather resistance test for 2000h, and the alkali resistance and water resistance are significantly improved;

[0057] 5. Good processability: storage stability of more than 12 months, easy construction and environmentally friendly.

[0058] The realization of these properties is due to the innovations of the present invention in molecular design, interface regulation and process optimization, which provides a new technical solution for the development of cement floor coatings. DETAILED DESCRIPTION

[0059] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0060] Example 1

[0061] A water-based coating suitable for cement floor and preparation method thereof

[0062] The water-based coating of this embodiment is prepared by the following components in parts by weight:

[0063] Among them, 60 parts of acrylic emulsion are selected, including pure acrylic emulsion and water-based acrylic ester emulsion mixed in a weight ratio of 4:1, the pure acrylic emulsion is styrene acrylic emulsion, and the water-based acrylic ester emulsion is a random copolymer of methyl methacrylate, ethyl acrylate and vinyl acetate.

[0064] Furthermore, 3 parts of N-hydroxyethyl acrylamide are selected, wherein the active double bond content is not less than 98%; 2 parts of modified nano-silica are selected; 0.1 parts of graphene oxide are selected, and the thickness of the layer is 0.8-1.2nm; 1 part of polyethylene glycol methyl ether methacrylate is selected, wherein the number of repeating units of the polyethylene glycol segment is 45; 2 parts of 2-(dimethylamino)ethyl methacrylate are selected, and the purity is ≥99%.

[0065] Preferably, the defoaming agent is 0.2 parts of organosilicon quaternary ammonium salt; the leveling agent is 0.5 parts of polydimethylsiloxane; the wetting agent is 0.3 parts of polyoxyethylene ether; and the film-forming aid is 4 parts of a 1:1 mixture of lauryl alcohol ester and propylene glycol methyl ether.

[0066] In particular, the thickener is selected from 0.5 parts of quaternary ammonium salt-modified hydroxyethyl cellulose, whose modification degree is 0.35-0.45; the mildew and fungicide is selected from 0.1 parts of a 1:2 mixture of 2-methyl-4-isothiazoline-3-one and 1,2-benzisothiazol-3(2H)-one; the filler is selected from stearic acid-modified ultrafine calcium carbonate (particle size 0.7 μm), nano zinc oxide (particle size 30 nm) and hollow glass microspheres (particle size 40 μm, density 0.21 g / cm 3 ) were mixed in a weight ratio of 3:1:1 for a total of 20 parts.

[0067] The preparation method comprises the following steps:

[0068] Firstly, the modified nano nitric acid dioxide is prepared. The specific steps are as follows: vacuum drying nano-silica with a particle size of 20 nm at 105° C. for 4 hours in order to fully remove surface adsorbed water; then preparing a mixed solution with a volume ratio of ethanol to water of 8:2, which can ensure moderate hydrolysis of the silane coupling agent; adding (3-glycidyl propoxy) trimethoxysilane to the mixed solution, adjusting the pH to 4 with glacial acetic acid, which is conducive to the hydrolysis of silane groups without causing too fast condensation; stirring at room temperature for 30 minutes for pre-hydrolysis to fully hydrolyze the silane coupling agent; dispersing the pretreated nano-silica in ethanol, ultrasonically dispersing for 15 minutes to form a stable suspension; then slowly adding the pre-hydrolyzed silane coupling agent solution at a rate of 2 mL / min, heating to 60° C., stirring for reaction for 4 hours, under which conditions, the surface silanol groups and the silane coupling agent can fully react; finally centrifuging at 8000 rpm, washing with ethanol 3 times to remove unreacted products, vacuum drying at 60° C. for 12 hours, and grinding through a 200-mesh sieve.

[0069] Secondly, prepare water-based coatings. The specific process is as follows: mix acrylic emulsion with N-hydroxyethyl acrylamide at a stirring speed of 400r / min, which can ensure that the components are fully mixed without introducing too many bubbles; add the modified nano-silica and graphene oxide prepared above, and ultrasonically disperse at 30°C for 15 minutes. This temperature and time can make the nano-filler evenly dispersed without affecting the stability of the emulsion; under nitrogen protection, add polyethylene glycol methyl ether methacrylate and 2-(dimethylamino) ethyl methacrylate in turn, control the temperature at 45°C, and nitrogen protection can prevent pre-polymerization caused by free radicals; then add thickener and filler in turn, stir for 3 minutes until uniform; finally, add a mixed solution of defoamer, film-forming aid and leveling agent at a rate of 0.5g / min, and continue stirring for 30 minutes to obtain the finished product.

[0070] In this embodiment, by reasonably controlling the ratio of each component and the preparation process parameters, especially by optimizing the surface modification of nano-silicon dioxide and the dispersion process, the final product has excellent substrate wettability and adhesion. Among them, quaternary ammonium salt-modified hydroxyethyl cellulose is used as a thickener, which can provide sufficient viscosity under low shear conditions to prevent filler sedimentation, and the viscosity decreases rapidly during high shear construction, ensuring good construction performance.

[0071] Example 2

[0072] A water-based coating suitable for cement floor and preparation method thereof

[0073] The water-based coating of this embodiment is prepared by the following components in parts by weight:

[0074] Among them, 70 parts of acrylic emulsion are selected, including pure acrylic emulsion and water-based acrylic ester emulsion mixed in a weight ratio of 4:1, the pure acrylic emulsion is styrene acrylic emulsion, and the water-based acrylic ester emulsion is a random copolymer of methyl methacrylate, ethyl acrylate and vinyl acetate;

[0075] Furthermore, 4 parts of N-hydroxyethyl acrylamide are selected, wherein the active double bond content is not less than 98%; 3 parts of modified nano-silica are selected; 0.2 parts of graphene oxide are selected, and the thickness of the layer is 1.0-1.4nm; 1.5 parts of polyethylene glycol methyl ether methacrylate are selected, wherein the number of repeating units of the polyethylene glycol segment is 47; 3 parts of 2-(dimethylamino)ethyl methacrylate are selected, and the purity is ≥99%.

[0076] Preferably, the defoaming agent is 0.4 parts of organosilicon quaternary ammonium salt; the leveling agent is 0.8 parts of polydimethylsiloxane; the wetting agent is 0.5 parts of polyoxyethylene ether; and the film-forming aid is 7 parts of a 1:1 mixture of lauryl alcohol ester and propylene glycol methyl ether.

[0077] In particular, the thickener is 1.0 part of quaternary ammonium salt-modified hydroxyethyl cellulose, and the modification degree thereof is 0.45-0.55; the mildew and fungicide is 0.15 part of a 1:2 mixture of 2-methyl-4-isothiazoline-3-one and 1,2-benzisothiazol-3(2H)-one; the filler is stearic acid-modified ultrafine calcium carbonate (particle size 1.0 μm), nano zinc oxide (particle size 40 nm) and hollow glass microspheres (particle size 50 μm, density 0.23 g / cm 3 ) were mixed in a weight ratio of 3:1:1 for a total of 30 parts.

[0078] The preparation method comprises the following steps:

[0079] First, prepare modified nano-silica. The specific steps are: vacuum dry nano-silica with a particle size of 25nm at 105℃ for 4h; prepare a mixed solution with a volume ratio of ethanol to water of 8:2; add (3-glycidyl propoxy) trimethoxysilane to the mixed solution, adjust the pH to 4.5 with glacial acetic acid, and this pH value can achieve a moderate hydrolysis rate of the silane coupling agent; stir at room temperature for 30min for pre-hydrolysis; disperse the pretreated nano-silica in ethanol and ultrasonically disperse for 15min; then slowly add the pre-hydrolyzed silane coupling agent solution at a rate of 2.5mL / min, heat to 60℃, stir and react for 4h; finally centrifuge at 8000rpm, wash with ethanol 3 times, vacuum dry at 60℃ for 12h, and grind through a 200-mesh sieve.

[0080] Secondly, prepare water-based coatings: mix acrylic emulsion and N-hydroxyethyl acrylamide at a stirring speed of 500 r / min; add the prepared modified nano-silica and graphene oxide, and ultrasonically disperse at 32°C for 18 minutes; under nitrogen protection, add polyethylene glycol methyl ether methacrylate and 2-(dimethylamino)ethyl methacrylate in turn, and control the temperature at 48°C; add thickener and filler in turn, and stir for 3 minutes; finally, add defoamer, film-forming aid and leveling agent dropwise at a rate of 0.8 g / min, and continue stirring for 35 minutes.

[0081] In this embodiment, the crosslinking density of the coating is significantly enhanced by increasing the amount of N-hydroxyethyl acrylamide and optimizing the mixing process with the emulsion. At the same time, the increase in the content of modified nano-silicon dioxide and the optimized surface modification process further enhance the mechanical strength and durability of the coating.

[0082] Example 3

[0083] A water-based coating suitable for cement floor and preparation method thereof

[0084] The water-based coating of this embodiment is prepared by the following components in parts by weight:

[0085] Among them, the acrylic emulsion is selected to be 75 parts, including pure acrylic emulsion and water-based acrylic ester emulsion mixed in a weight ratio of 4:1, the pure acrylic emulsion is styrene acrylic emulsion, and the water-based acrylic ester emulsion is a random copolymer of methyl methacrylate, ethyl acrylate and vinyl acetate;

[0086] Furthermore, 4.5 parts of N-hydroxyethyl acrylamide are selected, wherein the active double bond content is not less than 98%; 3.5 parts of modified nano-silica are selected; 0.25 parts of graphene oxide are selected, and the thickness of the layer is 1.2-1.6nm; 1.8 parts of polyethylene glycol methyl ether methacrylate are selected, wherein the number of repeating units of the polyethylene glycol segment is 48; and 3.5 parts of 2-(dimethylamino)ethyl methacrylate are selected.

[0087] Preferably, the defoaming agent is 0.5 parts of organosilicon quaternary ammonium salt; the leveling agent is 0.9 parts of polydimethylsiloxane; the wetting agent is 0.5 parts of polyoxyethylene ether; and the film-forming aid is 8 parts of a 1:1 mixture of lauryl alcohol ester and propylene glycol methyl ether.

[0088] In particular, the thickener is 1.2 parts of quaternary ammonium salt-modified hydroxyethyl cellulose, and the modification degree is 0.55-0.65; the mildew and fungicide is 0.18 parts of a 1:2 mixture of 2-methyl-4-isothiazoline-3-one and 1,2-benzisothiazol-3(2H)-one; the filler is stearic acid-modified ultrafine calcium carbonate (particle size 1.1 μm), nano zinc oxide (particle size 45 nm) and hollow glass microspheres (particle size 55 μm, density 0.24 g / cm 3 ) were mixed in a weight ratio of 3:1:1 for a total of 35 parts.

[0089] The preparation method comprises the following steps:

[0090] First, prepare modified nano-silica. The specific steps are: vacuum dry nano-silica with a particle size of 28nm at 105℃ for 4h; prepare a mixed solution with a volume ratio of ethanol to water of 8:2; add (3-glycidyl propoxy) trimethoxysilane to the mixed solution, and adjust the pH to 4.8 with glacial acetic acid; stir at room temperature for 30min for pre-hydrolysis; disperse the pre-treated nano-silica in ethanol and ultrasonically disperse for 15min; then slowly add the pre-hydrolyzed silane coupling agent solution at a rate of 2.8mL / min, heat to 60℃, stir and react for 4h; finally centrifuge at 8000rpm, wash with ethanol 3 times, vacuum dry at 60℃ for 12h, and grind through a 200-mesh sieve.

[0091] Secondly, prepare water-based coatings: mix acrylic emulsion and N-hydroxyethyl acrylamide at a stirring speed of 550 r / min; add the prepared modified nano-silica and graphene oxide, and ultrasonically disperse at 33°C for 19 minutes; under nitrogen protection, add polyethylene glycol methyl ether methacrylate and 2-(dimethylamino)ethyl methacrylate in turn, and control the temperature at 48°C; add thickener and filler in turn, and stir for 3 minutes; finally, add defoamer, film-forming aid and leveling agent at a rate of 0.9 g / min, and continue stirring for 38 minutes.

[0092] In this embodiment, by increasing the amount of functional components and optimizing their ratio, especially increasing the content of film-forming aids, the film-forming performance and weather resistance of the coating are significantly improved. At the same time, the increased filler content and optimized particle size distribution provide better mechanical properties and surface effects.

[0093] Example 4

[0094] A water-based coating suitable for cement floor and preparation method thereof

[0095] The water-based coating of this embodiment is prepared by the following components in parts by weight:

[0096] Among them, 80 parts of acrylic emulsion are selected, including pure acrylic emulsion and water-based acrylic ester emulsion mixed in a weight ratio of 4:1, the pure acrylic emulsion is styrene acrylic emulsion, the water-based acrylic ester emulsion is a random copolymer of methyl methacrylate, ethyl acrylate and vinyl acetate, and the glass transition temperature of the random copolymer is 25-30°C;

[0097] Furthermore, 5 parts of N-hydroxyethyl acrylamide are selected, wherein the active double bond content is not less than 98%; 4 parts of modified nano-silica are selected; 0.3 parts of graphene oxide are selected, and the thickness of the layer is 1.4-1.8nm; 2 parts of polyethylene glycol methyl ether methacrylate are selected, wherein the number of repeating units of the polyethylene glycol segment is 50; 4 parts of 2-(dimethylamino)ethyl methacrylate are selected, and the purity is ≥99%.

[0098] Preferably, the defoaming agent is 0.6 parts of organosilicon quaternary ammonium salt; the leveling agent is 1 parts of polydimethylsiloxane; the wetting agent is 0.6 parts of polyoxyethylene ether; and the film-forming aid is 10 parts of a 1:1 mixture of lauryl alcohol ester and propylene glycol methyl ether.

[0099] In particular, the thickener is 1.5 parts of quaternary ammonium salt-modified hydroxyethyl cellulose, and the modification degree is 0.65-0.75; the mildew and fungicide is 0.2 parts of a 1:2 mixture of 2-methyl-4-isothiazoline-3-one and 1,2-benzisothiazol-3(2H)-one; the filler is stearic acid-modified ultrafine calcium carbonate (particle size 1.2 μm), nano zinc oxide (particle size 50 nm) and hollow glass microspheres (particle size 60 μm, density 0.25 g / cm 3 ) were mixed in a weight ratio of 3:1:1 for a total of 40 parts.

[0100] The preparation method comprises the following steps:

[0101] First, prepare modified nano-silica. The specific steps are: vacuum dry nano-silica with a particle size of 30nm at 105℃ for 4h; prepare a mixed solution with a volume ratio of ethanol to water of 8:2; add (3-glycidyl propoxy) trimethoxysilane to the mixed solution, adjust the pH to 5.0 with glacial acetic acid; stir at room temperature for 30min for pre-hydrolysis; disperse the pre-treated nano-silica in ethanol, and ultrasonically disperse for 15min; then slowly add the pre-hydrolyzed silane coupling agent solution at a rate of 3.0mL / min, heat to 60℃, stir and react for 4h; finally centrifuge at 8000rpm, wash with ethanol 3 times, vacuum dry at 60℃ for 12h, and grind through a 200-mesh sieve.

[0102] Secondly, prepare water-based coatings: mix acrylic emulsion and N-hydroxyethyl acrylamide at a stirring speed of 600 r / min; add the prepared modified nano-silica and graphene oxide, and ultrasonically disperse at 35°C for 20 minutes; under nitrogen protection, add polyethylene glycol methyl ether methacrylate and 2-(dimethylamino)ethyl methacrylate in turn, and control the temperature at 50°C; add thickener and filler in turn, and stir for 3 minutes; finally, add defoamer, film-forming aid and leveling agent dropwise at a rate of 1.0 g / min, and continue stirring for 40 minutes.

[0103] In the present embodiment, by further increasing the content of each functional component and optimizing its ratio, the coating system forms a more complete synergistic network structure. In particular, the synergistic effect of the higher content of pH responsive component 2-(dimethylamino)ethyl methacrylate and modified nano-silica forms a dynamic cross-linked network during the coating curing process, significantly improving the mechanical strength and durability of the coating. At the same time, the increased filler system further optimizes the overall performance of the coating through the multi-scale enhancement effect. In addition, the increased thickener dosage and degree of modification ensure that the system still has good stability and construction performance under high filling conditions.

[0104] It can be seen from the above four embodiments that the present invention achieves a synergistic effect among the components by precisely controlling the ratio of the components and their preparation process. The optimized formula not only exhibits excellent construction performance, but also has outstanding durability and mechanical properties, providing a new technical solution for the application of cement floor coatings.

[0105] Comparative Example 1 (corresponding to Example 1)

[0106] A water-based coating suitable for cement floor and preparation method thereof

[0107] This comparative example adopts a formula similar to that of Example 1, but does not add N-hydroxyethyl acrylamide and modified nano-silica. The specific component ratio (by weight) is: 60 parts of acrylic emulsion, 0.1 parts of graphene oxide, 1 part of polyethylene glycol methyl ether methacrylate, 2 parts of 2-(dimethylamino)ethyl methacrylate, 0.2 parts of defoamer, 0.5 parts of leveling agent, 0.3 parts of wetting agent, 4 parts of film-forming aid, 0.5 parts of thickener, 0.1 parts of mildew and fungicide, and 20 parts of filler. The specific selection of each component is the same as that of Example 1.

[0108] The preparation method is basically the same as that of Example 1, but the preparation step of modified nano-silica is omitted. The results show that due to the lack of the cross-linking network provided by N-hydroxyethyl acrylamide and the reinforcing effect of modified nano-silica, the adhesion of the coating is significantly reduced, the water resistance is reduced by more than 50%, and obvious blistering occurs in repeated immersion tests.

[0109] Comparative Example 2 (corresponding to Example 2)

[0110] A water-based coating suitable for cement floor and preparation method thereof

[0111] This comparative example adopts a formula similar to that of Example 2, but replaces the nano-silicon dioxide with raw materials that have not been surface-modified. The amounts of each component in the formula are the same as those of Example 2, wherein the modified nano-silicon dioxide is replaced by 3 parts of unmodified nano-silicon dioxide.

[0112] The preparation process was the same as that of Example 2, but the surface modification step of nano-silicon dioxide was omitted. The results showed that due to the poor compatibility of nano-silicon dioxide with the organic phase, obvious agglomeration occurred, resulting in a 30% decrease in the mechanical properties of the coating and an increase in surface roughness.

[0113] Comparative Example 3 (corresponding to Example 3)

[0114] A water-based coating suitable for cement floor and preparation method thereof

[0115] This comparative example adopts a formula similar to that of Example 3, but does not add 2-(dimethylamino)ethyl methacrylate. Other components and amounts remain unchanged, and the total amount of the formula is supplemented by adding acrylic emulsion.

[0116] The preparation process is the same as that of Example 3, but the step of adding 2-(dimethylamino)ethyl methacrylate is omitted. The results show that the rheological properties of the coating during construction are significantly deteriorated due to the lack of the pH responsive component, and the stability of the cured coating in an alkaline environment is reduced, and the durability is reduced by 40%.

[0117] Comparative Example 4 (corresponding to Example 4)

[0118] A water-based coating suitable for cement floor and preparation method thereof

[0119] This comparative example adopts a formula similar to that of Example 4, but the filler system is changed to 40 parts of calcium carbonate alone, thereby eliminating the compounding effect of nano zinc oxide and hollow glass microspheres.

[0120] The preparation process is the same as that of Example 4, but the filler mixing step is simplified. The results show that due to the lack of synergistic effect of multi-stage fillers, the mechanical strength of the coating is reduced by 45%, and the surface wear resistance is significantly reduced.

[0121] Comparative Example 5 (corresponding to Example 1)

[0122] A water-based coating suitable for cement floor and preparation method thereof

[0123] In this comparative example, the thickener in Example 1 was replaced with ordinary hydroxyethyl cellulose (not modified with quaternary ammonium salt), and the amount was kept unchanged at 0.5 parts. The other components and amounts were the same as those in Example 1.

[0124] The preparation process is the same as that of Example 1. The results show that after using the unmodified thickener, the coating exhibits obvious stratification during storage, has poor leveling during construction, and the surface quality of the cured coating is significantly reduced.

[0125] Comparative Example 6 (corresponding to Example 4)

[0126] A water-based coating suitable for cement floor and preparation method thereof

[0127] This comparative example adopts a formula similar to that of Example 4, but the film-forming aid is changed to 10 parts of a single lauryl alcohol ester, thereby eliminating the synergistic effect of the two-component film-forming aid.

[0128] The preparation process is the same as that of Example 4, but the mixing step of the film-forming aid is simplified. The results show that the minimum film-forming temperature of the coating increases, incomplete film formation occurs in a low temperature environment, and the flexibility of the coating decreases by 25%.

[0129] From the above comparative examples, we can see that:

[0130] 1. The synergistic effect of N-hydroxyethyl acrylamide and modified nano-silica is crucial to improving coating adhesion and water resistance;

[0131] 2. The surface modification of nano-silica plays a decisive role in improving the filler dispersion and coating mechanical properties;

[0132] 3. The introduction of pH-responsive components significantly improves the coating's construction performance and coating durability;

[0133] 4. The design of multi-stage filler system plays an important role in improving the comprehensive mechanical properties of coatings;

[0134] 5. The quaternary ammonium salt modification of the thickener has a significant impact on the system stability and construction performance;

[0135] 6. The synergistic effect of the two-component film-forming aid plays a key role in the film-forming properties and flexibility of the coating.

[0136] These comparison results fully demonstrate the necessity of the various innovative features of the present invention and the significance of the technical effects.

[0137] Performance testing and evaluation

[0138] According to the characteristics and application requirements of the water-based coating of the present invention, the following test items are designed, and all tests are carried out under a standard environment (23±2° C., relative humidity 50±5%).

[0139] 1. Adhesion test: The test method is carried out in accordance with GB / T9286-1998. The sample is coated on the pre-treated cement test block, and after curing for 7 days, the adhesion is tested by the cross-cut method. At the same time, the sample is immersed in 40℃ water for 7 days and then the adhesion is tested again to evaluate the water resistance.

[0140] 2. Cross-link density test: The cross-link density was determined by the gel content method. The cured coating sample was swollen with tetrahydrofuran for 24 hours, the swelling degree and gel content were determined, and the cross-link density was calculated according to the Flory-Rehner equation.

[0141] 3. Analysis of nanoparticle dispersion: The dispersion state of modified nano-silica was observed using a transmission electron microscope (TEM). Ultra-thin sections of the samples were negatively stained with phosphotungstic acid and observed at an accelerating voltage of 200 kV. Dynamic light scattering (DLS) was also used to determine the particle size distribution of the dispersion system.

[0142] 4. Interface structure characterization: Scanning electron microscopy (SEM) was used to observe the cross-sectional morphology of the coating and evaluate the dispersion state of the filler and the interface bonding condition. The sample was fractured by liquid nitrogen and observed at an accelerating voltage of 15 kV after gold spraying.

[0143] 5. Dynamic mechanical properties test: Use a dynamic mechanical analyzer (DMA) to test the dynamic mechanical properties of the coating. Test conditions: heating rate 3°C / min, frequency 1Hz, temperature range -50~150°C.

[0144] 6. Wear resistance test: According to GB / T1768-2006, using Taber abrasion tester, load 1000g, speed 60r / min, test the mass loss after 1000 revolutions.

[0145] The test results are shown in the following table:

[0146] [Table 1] Test results of basic coating properties

[0147]

[0148] [Table 2] Dynamic mechanical properties test results

[0149]

[0150] It can be seen from the test results that Example 4 exhibits the best comprehensive performance, which is mainly due to the synergistic effects of the following aspects:

[0151] 1. Molecular level synergistic mechanism: Through TEM observation, it was found that the modified nano-silica was uniformly dispersed in the matrix, and the particle size distribution was in the range of 25-35nm. DLS test showed that the polydispersity index (PDI) of the dispersion system was less than 0.2, indicating excellent dispersion uniformity. This good dispersion state is due to the improved interfacial compatibility brought about by the modification of silane coupling agent, and the introduction of N-hydroxyethyl acrylamide further enhanced the compatibility of the system.

[0152] 2. Interface enhancement mechanism: SEM observation shows that the cross section of Example 4 presents typical toughness fracture characteristics, the filler and the matrix interface are tightly bonded, and there is no obvious interface debonding phenomenon. This is mainly due to the chemical reaction between the epoxy groups on the surface of the modified nano-silica and the matrix to form a chemically bonded interface layer. At the same time, the amphiphilic structure of polyethylene glycol methyl ether methacrylate forms an orderly arrangement at the interface, further optimizing the interface structure.

[0153] 3. Dynamic cross-linking network formation mechanism: DMA test results show that Example 4 has the widest glass transition range and the highest tanδ peak temperature, which indicates that the system forms a network structure with different cross-linking densities. The formation of this network structure originates from the dynamic cross-linking effect of the pH-responsive component during the film formation process, so that the coating has sufficient cross-linking density to ensure mechanical properties and maintains appropriate segment mobility to provide toughness.

[0154] The present invention has the following unexpected technical effects:

[0155] 1. Water resistance performance beyond expectation: Example 4 performed well in the water resistance test, and the adhesion remained at level 0 after immersion in water for 7 days, without any blistering or cracking. This is far better than the expected performance indicators, and analysis shows that this is the result of multiple barrier effects: the lamellar structure of the nanofiller, the dense structure of the dynamic cross-linked network, and the interfacial chemical bonding.

[0156] 2. Excellent low-temperature flexibility: In the -20°C impact test, the sample of Example 4 still maintains good flexibility, which is a performance that is difficult to achieve for a water-based coating system. This is mainly due to the multi-scale network structure formed by the system. Networks of different scales provide different chain segment movement capabilities, ensuring toughness at low temperatures.

[0157] 3. Self-repairing ability: During the wear test, it was found that the surface of the sample of Example 4 was able to partially self-repair at room temperature after being slightly scratched. This phenomenon may be due to the dynamic reversible bonds formed by the pH-responsive component on the surface. This discovery provides a new idea for the development of smart coating materials.

[0158] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A water-based paint suitable for cement floors, characterized in that: The water-based coating comprises the following components by weight: Acrylic emulsion 60-80 parts, 3-5 parts of N-hydroxyethyl acrylamide, 2-4 parts of modified nano silicon dioxide, Graphene oxide 0.1-0.3 parts, 1-2 parts of polyethylene glycol methyl ether methacrylate, 2-(dimethylamino)ethyl methacrylate 2-4 parts, Defoaming agent 0.2-0.6 parts, 0.5-1 part of leveling agent, Wetting agent 0.3-0.6 parts, 4-10 parts of film-forming aid, Thickener 0.5-1.5 parts, 0.1-0.2 parts of antifungal fungicide, 20-40 parts of filler.

2. The water-based paint according to claim 1, characterized in that: The acrylic emulsion includes pure acrylic emulsion and water-based acrylic ester emulsion, and the weight ratio of the pure acrylic emulsion to the water-based acrylic ester emulsion is 4:1; wherein the pure acrylic emulsion is styrene acrylic emulsion, and the water-based acrylic ester emulsion is selected from random copolymers of methyl methacrylate, ethyl acrylate and vinyl acetate.

3. The water-based paint according to claim 1, characterized in that: The modified nano silicon dioxide is nano silicon dioxide modified by (3-glycidyl propoxy) trimethoxy silane, and the particle size of the nano silicon dioxide is 20-30 nm.

4. The water-based paint according to claim 1, characterized in that: The thickener is quaternary ammonium salt-modified hydroxyethyl cellulose, the mildew and fungicide includes a mixture of 2-methyl-4-isothiazoline-3-one and 1,2-benzisothiazol-3(2H)-one, with a weight ratio of 1:2, and the filler includes modified calcium carbonate, nano zinc oxide and hollow glass microspheres, with a weight ratio of 3:1:

1.

5. The water-based paint according to claim 1, characterized in that: The number of repeating units of the polyethylene glycol segment in the polyethylene glycol methyl ether methacrylate is 45-50, the defoaming agent is a quaternary ammonium salt of organic silicon, the leveling agent is polydimethylsiloxane, and the wetting agent is polyoxyethylene ether.

6. The water-based paint according to claim 1, characterized in that: The film-forming aid is selected from a mixture of lauryl alcohol ester and propylene glycol methyl ether, and the weight ratio of the lauryl alcohol ester to propylene glycol methyl ether is 1:

1.

7. A method for preparing the water-based coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Preparation of modified nano-silicon dioxide: The nano-silica was dried in vacuum at 105 °C for 4 h; An ethanol / water mixed solution was prepared, wherein the volume ratio of ethanol to water was 8:2; Add (3-glycidylpropoxy)trimethoxysilane to the mixed solution and adjust the pH to 4-5; Stir at room temperature for 30 min for pre-hydrolysis; The pretreated nano-silica was dispersed in ethanol and ultrasonically dispersed for 15 min; Slowly add the pre-hydrolyzed silane coupling agent solution, raise the temperature to 60°C, and stir to react for 4 hours; The mixture was centrifuged, washed with ethanol three times, dried under vacuum at 60 °C for 12 h, and ground through a 200-mesh sieve; (2) Preparation of water-based coatings: Mix the acrylic emulsion with N-hydroxyethyl acrylamide at a stirring speed of 400-600 r / min; Add the modified nano-silicon dioxide and graphene oxide obtained in step (1), and disperse by ultrasonic for 15-20 minutes; Add polyethylene glycol methyl ether methacrylate and 2-(dimethylamino)ethyl methacrylate in sequence, and control the temperature at 45-50°C; Add thickener and filler in sequence and stir for 3 minutes; Add defoamer, film-forming aid and leveling agent dropwise at a rate of 0.5-1 g / min and continue stirring for 30 min.

8. The method according to claim 7, characterized in that In the step (2), nitrogen protection is used when adding polyethylene glycol methyl ether methacrylate and 2-(dimethylamino)ethyl methacrylate.

9. The method according to claim 7, characterized in that: In the step (2), when adding the modified nano-silicon dioxide and graphene oxide, the dispersion temperature is controlled at 30-35°C.

10. The water-based paint according to claim 1, characterized in that: The modified calcium carbonate is stearic acid-modified ultrafine calcium carbonate with a particle size of 0.7-1.2 μm; the particle size of the nano zinc oxide is 30-50 nm; the particle size of the hollow glass microsphere is 40-60 μm, and the density is 0.21-0.25 g / cm 3 .

Citation Information

Patent Citations

  • Nano-material modified type I polymer cement waterproof coating and prepration method thereof

    CN101555114A

  • Nanometric and aqueous coating

    CN104559589A

  • High-wear-resistant antibacterial acrylate paint

    CN106366899A

  • Graphene water-based super-wear-resisting floor paint and preparation method thereof

    CN108059860A

  • Water-based inorganic floor coating and preparation method thereof

    CN111253810A

Cited By

  • High-adhesion acrylic coating and preparation method thereof

    CN120290058A

  • A high-adhesion acrylic coating and its preparation method

    CN120290058B

  • High-rheology lasting coating and preparation method thereof

    CN121673919A